2020
DOI: 10.1080/10942912.2020.1733015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of proximate compositions and taste attributes of three Asian hard clams (Meretrix meretrix) with different shell colors

Abstract: Meretrix meretrix with three shell colors (mottled shell, red shell, yellow shell) were analyzed for nutritive and taste attributes. Additionally, the influence of cooking on the taste active components was also evaluated. The three kinds of clams had higher crude protein contents. Alanine, glutamic acid, arginine, 5ʹ-adenosine monophosphate, Cl − , Na + , K + and PO 4 3were the major taste compounds of Meretrix meretrix. In addition to PO 4 3-, the contents of all major taste compounds decreased after cooking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Soft tissues of C. erycina is a high protein and moisture, and low-fat food based on its proximate composition (Table 1). Such composition is typical of other bivalve molluscs [16,17]. Similar to the Meretrix lusoria [18], it was established that the moisture content of the clams C. erycina soft tissues is 77.86±0.74 g/100 g wet soft tissues weight.…”
Section: Percentage Edibility (Pe) Condition Index (Ci) and Proximatsupporting
confidence: 55%
“…Soft tissues of C. erycina is a high protein and moisture, and low-fat food based on its proximate composition (Table 1). Such composition is typical of other bivalve molluscs [16,17]. Similar to the Meretrix lusoria [18], it was established that the moisture content of the clams C. erycina soft tissues is 77.86±0.74 g/100 g wet soft tissues weight.…”
Section: Percentage Edibility (Pe) Condition Index (Ci) and Proximatsupporting
confidence: 55%
“…Additionally, the presence of a high glutamic acid content is in accordance with the previous report for the snail Cookia sulcata (138–141 mg/g protein DM), while this species had lower aspartic acid (69–70 mg/g protein DM) than the value obtained in the present study [ 67 ]. In the present study, alanine and glycine were also found in high concentrations, which enhances the pleasant sweet–umami taste of C. saturnus meat [ 68 ]. It has also been reported that, because amino acids participate in Maillard reactions when heated during processing conditions, their high concentration may also affect flavor due to the generation of volatile compounds [ 69 ].…”
Section: Resultsmentioning
confidence: 82%
“…The 5′-nucleotides(GMP, IMP, and AMP) were extracted and analyzed on a HPLC system (UltiMate 3000, Thermo Fisher Scientific Co., Ltd., Massachusetts, USA), according to the method modified from Wen et al (2020) . A chromatographic column (Acclaim PolarAdvantage II C18, 50 mm × 4.6 mm, 3 μm) with mobile phase A of methanol and mobile phase B of 20 mM KH 2 PO 4 -K 2 HPO 4 buffer solution (v/v = 1:1, pH = 5.8).…”
Section: Methodsmentioning
confidence: 99%
“…The contents of sodium (Na + ), potassium (K + ), phosphate (PO 4 3- ), and chlorine (Cl - ) were determined using an inductive coupled plasma mass spectrometer (ICP-MS, Thermo Fisher Scientific Co., ltd., Massachusetts, USA) and the method used by Wen et al (2020) . The ICP-MS was equipped with a detector (DS5 defection stabilizer), a suppressor (AERS500), and an anion exchange column (AS14).…”
Section: Methodsmentioning
confidence: 99%